2018
DOI: 10.3389/fphys.2018.01504
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for Endurance Competitions at Altitude: Physiological, Psychological, Dietary and Coaching Aspects. A Narrative Review

Abstract: It was the Summer Olympic Games 1968 held in Mexico City (2,300 m) that required scientists and coaches to cope with the expected decline of performance in endurance athletes and to establish optimal preparation programs for competing at altitude. From that period until now many different recommendations for altitude acclimatization in advance of an altitude competition were proposed, ranging from several hours to several weeks. Those recommendations are mostly based on the separate consideration of the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 143 publications
(187 reference statements)
0
47
0
1
Order By: Relevance
“…Exercising heart rates decrease with increasing SpO 2 during acclimatization exhibiting a similar time course [ 93 ]. In contrast to the aerobic capacity (VO 2 max), the initially reduced submaximal endurance performance at acute altitude improves during 2 to 3 weeks of acclimatization, accompanied by characteristic changes in cardiorespiratory responses [ 99 , 100 , 101 , 102 ]. For instance, the study by Horstman et al reported a 31% and 59% improvement on day 9 and 15 without considerable changes until day 22 [ 99 ].…”
Section: Part 3: Discussionmentioning
confidence: 99%
“…Exercising heart rates decrease with increasing SpO 2 during acclimatization exhibiting a similar time course [ 93 ]. In contrast to the aerobic capacity (VO 2 max), the initially reduced submaximal endurance performance at acute altitude improves during 2 to 3 weeks of acclimatization, accompanied by characteristic changes in cardiorespiratory responses [ 99 , 100 , 101 , 102 ]. For instance, the study by Horstman et al reported a 31% and 59% improvement on day 9 and 15 without considerable changes until day 22 [ 99 ].…”
Section: Part 3: Discussionmentioning
confidence: 99%
“…Major athletics events are rarely at high altitude, but athletes should prepare for the championships by training at the same altitude, adapting dietary strategies and with optimal psychological approach, alongside early arrival for acclimatization purposes (Burtscher et al, 2018).…”
Section: Environmentalmentioning
confidence: 99%
“…During exposure to a high altitude environment, the human body undergoes many physiological, biochemical, and haematological changes which are required for coping with the environmental stress at high altitude [5]. The physiological and biochemical adjustments include hyperventilation, in ammation, an increase in breathing capacity, and hemoglobin concentration that help to restore oxygen delivery to tissues despite low partial pressure [2,6,7]. Besides, the hormonal imbalance, shift in metabolic systems to lipid metabolism are in uenced by hypobaric hypoxia at high altitude [2].…”
Section: Introductionmentioning
confidence: 99%